Adaptation Short Story into Short Film - W W Legowo; Y A Ekawardhani (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to determine the changes that occur in the adaptation process of the short story “Berangkat” (Go) written by Akhmad Sekhu, into the short film “Krenteg” (Intention) written and directed by Marjo Klengkam Sulam. In collecting data, this study used a qualitative descriptive method. The analysis process is by reading the short story “Berangkat”, watching the short film “Krenteg”, study to personal communication with writer and filmmaker, identifying form of change, categorizing, describing, then concluding. Based on data analysis, it is concluded that there has been a change in the intrinsic elements of the short story “Berangkat” in the short film “Krenteg”. Such as changes to the title, characters, events, setting, plot, and language. These changes were made to strengthen the story and to bring out local wisdom. Changes divided into three categories: reduce, increase, and varying changes. In conveying the message, short stories use written media and short films use audio-visual media. When changing the media, there will be adjustments based on expression needs. The results of this study can be a reference for short film makers who want to adapt short stories and attract their interest in local wisdom.